The Role Of Service Quality Based On Digital Applications In Improving Customer Satisfaction Of Syariah Bank In Riau - Syahpawi, Syahpawi; Selamat, Kasmuri; Rustam, Rustam (LPPM ISNJ Bengkalis, 2025)
The purpose of this study is to conduct an in-depth study related to the role of service quality in increasing customer satisfaction of Islamic banks in Indonesia which is maximized by digital applications (mobile banking) and religiosity as an intervening variable. This effort was carried out with a quantitative approach as a research method and determined the number of samples as many as 110 respondents using the Yamame formula from a population size whose number is not known for certain, especially bank customers in general whose identities are kept secret. The technique of distributing questionnaires with accidental. While to conduct data analysis other than by multiple regression and MRA. The results of the test and disclosure are known that the quality of digital-based services plays a positive and significant role in increasing customer satisfaction both without and being intervened by religious values. The increase in service quality is not only caused by reliability, responsiveness, assurance, empathy and physical evidence, but the values ​​of Islamic religiosity strengthen customers to use digital applications (mobile banking).